(untitled) (Bangladesh Journal of Child Health, 2024)
Background: Children with diabetic ketoacidosis (DKA) suffer from several complications. Among them acute kidney injury (AKI) is one of the grave complications. Objectives: To determine the risk factors for development of AKI in children (age <15 years) with DKA and observe the outcome of these children. Method: An observational study was done in Department of Paediatrics, BIRDEM General Hospital, Dhaka, Bangladesh from January 2019 to December 2020. During study period, we observed all children with DKA who developed AKI. Data of clinical and biological variables were taken from hospital records and analysed. The parameters of children with AKI were compared with children with DKA who did not develop AKI. Then outcome of the children with AKI were measured. Statistical analysis was done by using SPSS version 23. Results: Among 73 children with DKA, 16 (21.9%) children developed AKI. Children were divided into two groups, DKA with AKI and DKA without AKI. No statistically significant differences were found in demographic features of children in both groups. We observed that, delay in initiation of treatment, low Glasgow Coma Scale (score- <8), haemodynamic failure, severe acidosis and sepsis were significant risk factors of developing AKI. Out of 16 children with AKI, 9(56.2%) patients needed peritoneal dialysis and 7(43.7%) responded to fluid resuscitation. Complete resolution occurred in 13(81.2%). Total mortality in DKA children was 13(17.8%). Among them 84.6% children died due to AKI. Conclusions: This study documented that 21.9% of children with DKA developed AKI. Among them mortality was 84.5%. BANGLADESH J CHILD HEALTH 2023; VOL 47 (1) : 30-33